Assessment of pre- and post-operative nutritional status in patients undergoing orthognathic surgery - Castro, Geórgia Alvares de; Castro, Vanessa Alvares de; Patin, Rose; Nogueira-de-Almeida, Carlos Alberto (Medicina (Ribeirao Preto), 2020)
Introduction: The maxillofacial procedures for skeletal deformities are characterized by structural-morphological changes derived from unfavorable genetics with diagnosis performed during craniofacial growth. Orthognathic surgery requires a total restriction on chewing for 60 days, leading to loss of body weight in overweight and obese individuals, as well as in well-nourished patients. Objective: Evaluating the pre- and post-operative nutritional status of patients undergoing orthognathic surgery. Material and methods: This is an interventional study. The study group received supplementation with whey protein, L-arginine, L-glutamine, and fatty acid Omega-3, and both groups were assessed in terms of anthropometric and biochemical measurements. The evaluation of soft tissue healing was conducted after surgery. Results: It is possible to infer that the percentage of skeletal muscle mass tends to increase in the intervention group, however, the weight loss was greater (-4.88%). Uric acid increased post-operative in the control group (+37.64%). Conclusion: Oral nutritional supplementation used in the study seems promising for reducing the loss of skeletal muscle mass, but further studies involving a larger number of patients are needed to confirm the results.